Laser additive processing of a functionally graded internal fracture fixation plate. (15th September 2017) - Lima, D.D.; Mantri, S.A.; Mikler, C.V.; Contieri, R.; Yannetta, C.J.; Campo, K.N.; Lopes, E.S.; Styles, M.J.; Borkar, T.; Caram, R.; Banerjee, R.
Abstract: Although bone fracture fixation implants are crucial for fracture site stability, undesirable stress shielding will be problematic if stiffness mismatch between the bone and the fracture fixation implant is significant. Thus, the need for fracture fixation implant design that provides sufficient stability at the fracture site to avoid potential stress shielding that may be associated with modulus mismatch is paramount. This potential issue can be addressed efficiently by fabricating stiffness-graded (compositionally graded) titanium alloys with low elastic modulus (or stiffness) at the ends, comparable to the bone modulus; and higher elastic modulus at the center, close to the site of the fracture. Additive manufacturing processes such as laser engineered net shaping (LENS™), a near-net shape processing technology, has the potential to fabricate functionally graded biomedical implants. This study focuses on the development of a novel LENS™ deposited, compositionally and functionally graded Ti-based metallic plate for potential bone fixation. The gradation has been achieved between a low modulus Ti-35Nb-15Zr (wt%) alloy and the higher modulus, commercially pure Ti near the center of the plate. Site-specific microstructure and mechanical properties along the compositional gradient are presented. Graphical abstract: Highlights: LENS™ based additive-manufacturing was used to deposit functionally graded biomaterial for a fracture-fixation plate. The fracture-fixation plate with elastic modulus varying between 70-110 GPa was obtained by varying the composition. The issue of stiffness mismatch between the bone and fracture plate is overcome by using the additively manufactured FGM.